Erosion and Accretion Characteristics of the Muddy Coast in the Central Coastal Area of Jiangsu Province Based on Long-Term Remote Sensing Monitoring - Qiqi Pan; Dong Zhang; Min Xu; Zhuo Zhang; Yunjuan Gu (Remote Sensing)
Owing to the abundant land resources in the intertidal zone, the central coastal area of Jiangsu Province, China, has implemented large-scale activities such as tidal flat reclamation, aquaculture, and harbor construction, which have strongly affected the local hydrodynamic environment and the evolution of the mudflat. In this study, based on the 1984–2022 multisource remote sensing image data, an enhanced waterline method (EWM) combined with an average slope method (ASM) were adopted to obtain the spatial–temporal evolution characteristics of the continental coastline and intertidal zone in central Jiangsu Province for six typical years, exhibiting the coastal variations at critical year intervals in response to former large-scale coastal development and subsequent coastal zone protection. Results showed that the coastlines significantly advanced toward the sea. The deposited coast moved toward the seaside at an annual rate of 85.91 m, and the reclaimed coast advanced toward the seaside at a yearly rate of 129.25 m, which were dominated by natural siltation and reclamation activities of mudflats. In the past forty years, the coast’s erosion and siltation transition node has gradually moved southward from the Sheyang Estuary to the Simaoyou Estuary. Affected by reclamation and coastal erosion, the most drastic changes in the slope of the erosive intertidal zone occurred in the section from Binhai Port to the Biandan Estuary, ranging from 2‰ to 14‰. The silted coastal section from the Sheyang Estuary to the Xinyang Estuary increased in average slope from 0.89‰ to 2.43‰ as a result of the continuous intensification of erosion. The area of the intertidal mudflat decreased by 47.76% from 1378.59 to 720.11 km2, whereas the mean width of the intertidal zone decreased by 48.02%, from 5518.44 m to 2868.36 m. This study provides current situations of the dynamic changes in the muddy coast of the central Jiangsu coast, which could be a comparison and reference for the sustainable development, utilization, and protection of similar muddy coasts globally.